The Influence of Future Anxiety on Students' Tendency to Experience Insomnia - Nurul Fitriana Ahmad; Sitti Murdiana; Haffiza Nur (ILIN Institute Makassar, 2024)
The study aims to determine the influence of future anxiety on the tendency of Makassar State University students to experience insomnia. A quantitative regression approach was employed. Respondents were 70 Makassar State University students. The sampling method was non-probability using accidental techniques. The results showed that future anxiety significantly influenced the tendency of Makassar State University students to experience insomnia, which means that future anxiety influences the tendency of insomnia. This study is expected to be a foundation for further researchers who examine similar variables